SAT0105 Survival in first line of biologic agents in an apulian cohort of rheumatoid arthritis patients with occult hepatitis b virus infection. (15th June 2017) - Carlino, G; Fornaro, M; D'Onofrio, F; Maruotti, N; Semeraro, A; Zuccaro, C; Santo, L; Marsico, A; Bucci, R; Quarta, L; Casilli, O; Falappone, PCF; et al.
Abstract : Background: The occurrence of hepatitis B virus (HBV) infection may be a concern during the treatment of patients with Rheumatoid Arthritis (RA). We wondered whether a state of HBV occult infection (anti-HBcAg-pos, HBsAg-neg, HBV-DNA-neg) might influence the effectiveness of biological drugs in RA patients in real-world settings. Objectives: We performed a retrospective analysis to evaluate the survival on first line biologic drug of RA Apulian patients with HBV occult infection. Methods: We analyzed longitudinal data of 384 consecutive RA patients starting a first biological drug in a time frame from 1st January 2008 to 31st December 2014. Demographic and disease related characteristics were collected at baseline and at last observation visit. Baseline serological markers of HBV infection and causes of discontinuation of treatment were also recorded. Primary endpoint was the influence of anti-HBcAg-pos on drug survival, estimated by Kaplan-Meier life table analysis. Estimates hazard ratios (HRs) of drug discontinuation or achievement of Clinical Disease Activity Index (CDAI) based remission at last visit, adjusted for disease characteristics, biological drug class and anti-HBcAg-pos were computed by Cox-regression models. Results: No baseline demographic and disease characteristics difference between anti-HBcAg-pos and anti-HBcAg-neg RA patients were detected, except for DAS28 that was significantly higher in anti-HBcAg-pos group. Drug survival rate was significantly lower in anti-HBcAg-pos (57.6%, median survival time (95% CI) 54 months (38–69)) than in anti-HBcAg-neg patients (67.8%, median survival time (95% CI) 77 months (59–94)). Median survival time for ineffectiveness was 15 months (12–17) for anti-HBcAg-pos and 24 months (18–30) for anti-HBcAg-neg patients (p=0.04). Cox regression models showed a significant association between anti-HBcAg-neg (HR 0.60, 0.39–0.92) or RF/ACPA-neg (HR 1.69, 1.16–2.46) and drug discontinuation, while co-therapy with MTX (HR 2.14, 1.01–4.58) or with steroids (HR 0.38, 0.16–0.91), and RF/ACPA neg (HR 0.45, 0.21–0.95) were independently associated with the achievement of CDAI based remission. Conclusions: HBV occult infection seems to influence negatively the effectiveness of biological therapies in RA patients. However, being a real-life setting, unknown confounding factors might generate an apparent association or mask a true correlation between the HBcAb status and clinical outcomes. Disclosure of Interest: None declared